Peran Kepala Sekolah Dalam Menumbuhkan Budaya Islami Di Smk Muhammadiyah Gubug Grobogan - Muslimin, Muslimin, Prof. Dr. Abdul Ngalim M.M (2016)
The purpose of this research was to determine (1) Planning principals in growing Islamic culture in SMK Muhammadiyah Gubug Grobogan. (2) Implementation of the principals in growing Islamic culture in SMK Muhammadiyah Gubug Grobogan. (3) Evaluation of the implementation of the principals in growing Islamic culture in SMK Muhammadiyah Gubug Grobogan. (4) Factor supporting and inhibiting factor in fostering the implementation of the principal Islamic culture in SMK Muhammadiyah Gubug Grobogan. Data collection techniques using observation, interviews and documentation. Data analysis technique performed with data collection, data reduction, data presentation, and conclusion. Test the validity of the data in this study using triangulationThe results of this study were (1) Application of Islamic Culture in SMK Muhammadiyah Gubug Grobogan an education development efforts to realize the goal of education, with the activities that are the vertical or horizontal nature. (2) The growth of Islamic culture in SMK Muhammadiyah Gubug Grobogan, the principal role of the central driving force of the program that has been set, both programs that are vertically or horizontally (3) Evaluation of the implementation of the grower culture of Islamic SMK Muhammadiyah Gubug Grobogan said is enough managed based on the achievements during the program. a) activities that are vertically through: implementation of Dhuhr prayers in congregation b) activities that are horizontal: obey grammar school terttib, courtesy environment, students avoid adverse events (4) The supporting factors a) the active participation of all citizens of good schools principals, teachers, staff and students to participate in, b) program in accordance with the vision and mission of the school, c) support for supporting infrastructure such as b) the allocation of funds. Factors inhibiting a) factor of student discipline students who have not been consistent in implementing programs Keywords: Islamic culture, vocational, school principal